Child and youth mental health and wellbeing before and after returning to in-person learning in secondary schools in the context of COVID-19 - Qian, Lei; McWeeny, Robert; Shinkaruk, Cheryl; Baxter, Andrew; Cao, Bo; Greenshaw, Andy; Silverstone, Peter; Pazderka, Hannah; Wei, Yifeng (Frontiers in Public Health, 2023)
Background As children reintegrate with in-person classroom learning after COVID-19, health and education institutions should remain mindful of students’ mental health. There is a paucity of data on changes in students’ mental health before, during and after their return to in-person classroom learning. Methods We collected and analyzed data on self-reported wellbeing, general mental health, perceived stress, and help-seeking attitudes from grade 7–12 students in a Catholic school division in Canada (n = 258 at baseline; n = 132 at follow-up). Outcomes were compared according to demographic differences such as gender, grade level, experience accessing mental health services, and presence of support staff between baseline and follow-up. Effects of time points and each demographic variable on each outcome and on the prediction of students’ mental health were also analyzed. Results No significant differences were apparent for outcomes between baseline and follow-up. However, specific subgroups: junior high students, male students, students who had not accessed mental health services, and students who had access to support-staff had better outcomes than their counterparts. From baseline to follow-up, male students reported mental health decline [Mean = 11.79, SD = 6.14; Mean = 16.29, SD = 7.47, F(1, 333) = 8.36, p < 0.01]; students who had not accessed mental health services demonstrated greater stress [Mean = 20.89, SD = 4.09; Mean = 22.28, SD = 2.24, F(1, 352) = 6.20, p < 0.05]; students who did not specify a binary gender reported improved general mental health [Mean = 19.87, SD = 5.89; Mean = 13.00, SD = 7.40, F(1, 333) = 8.70, p < 0.01], and students who did not have access to support-staff improved help-seeking attitudes [Mean = 22.32, SD = 4.62; Mean = 24.76, SD = 4.81; F(1, 346) = 5.80, p < 0.05]. At each time point, students indicated parents, guardians, and close friends as their most-preferred help-seeking sources. High stress predicted lower wellbeing at baseline, but higher wellbeing at follow-up. Conclusion Students presented stable mental health. Subgroups with decreased mental health may benefit from extra mental health support through building capacity among teachers and health care professionals to support students following public health emergencies.